2020
DOI: 10.3390/ijerph17165722
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Relationship between Match Outcome and Match Performances during the 2019 FIBA Basketball World Cup: A Quantile Regression Analysis

Abstract: The FIBA Basketball World Cup is one of the most prominent sporting competitions for men’s basketball, with coaches interested in key performance indicators (KPIs) that give a better understanding of basketball competitions. The aims of the study were to (1) examine the relationship between match KPIs and outcome in elite men’s basketball; and (2) identify the most suitable analysis (multiple linear regression (MLR) vs. quantile regression (QR)) to model this relationship during the men’s basketball tournament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
(42 reference statements)
2
21
1
Order By: Relevance
“…Therefore, more effective offensive actions that lead to two-point field goals, such as dribble penetration or post play, and greater physical ability would heighten the likelihood of team success. Unexpectedly, we found that three-point percentage had no significant relationship with the match outcome, which is inconsistent with a prior study from Zhang et al (2020) who reported that three-point score was a KPI that significantly associated with match outcome for men's basketball matches at the FIBA World Cup. This may be partly explained by the differences in the anthropometrical characteristics between men's and women's players (Garcia-Gil et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, more effective offensive actions that lead to two-point field goals, such as dribble penetration or post play, and greater physical ability would heighten the likelihood of team success. Unexpectedly, we found that three-point percentage had no significant relationship with the match outcome, which is inconsistent with a prior study from Zhang et al (2020) who reported that three-point score was a KPI that significantly associated with match outcome for men's basketball matches at the FIBA World Cup. This may be partly explained by the differences in the anthropometrical characteristics between men's and women's players (Garcia-Gil et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…This may indicate that use of linear statistical approaches may underestimate the influence of free-throw percentage on the match outcome. However, differences between sexes may exist as a previous study for men's basketball reported that free-throw percentage was not the KPI that can significantly affect the match result based on both linear and non-linear approaches (Zhang et al, 2020), In this regard, differences in motor abilities between women and men basketball players may be a plausible reasons for the different trends regarding the relationship between free-throw percentage and match outcome.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The variables examined included independent variables (Table 1). Definitions of these variables can be found in the previous studies [7,15,27,28]. Each variable has its values that allow it to accurately define the actions and situations analyzed (Table 1).…”
Section: Situational Variablesmentioning
confidence: 99%